KRITIK TERHADAP PARADIGMA POSITIVISME - Dysmala, Emma (Sekolah Tinggi Hukum Bandung, 2013)
Positivism paradigm shows that a resource to obtain the knowledge is by using healthy mind and performing an observation. Using healthy mind is a potential; a means of obtaining,achieving, and also revealing the truth through observation, and finally finding concept, generalization, proposition, and theory.Keyword: paradigm; positivism